2017
DOI: 10.1080/08941939.2017.1296512
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Reduces NF-κB and Subsequent Cytokine Production as Protective Effect in a Rodent Animal Model of Lung Ischemia-Reperfusion Injury

Abstract: We conclude that apigenin given intraperitoneally can reduce activation of NF-κB and also attenuate the expression of TNFα, IL-6, and iNOS in a surgical model of LIRI. The surgical procedure itself can induce significant damage to the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Chronic vascular inflammation is closely related to AS development [36]. Previous studies have revealed that apigenin can protect against inflammation [22,23]. Thus, we examined the effects of apigenin on LPS-stimulated inflammation in RAW264.7 macrophages.…”
Section: Apigenin Inhibits the Activation Of Tlr-4/nf-κb Pathway In Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic vascular inflammation is closely related to AS development [36]. Previous studies have revealed that apigenin can protect against inflammation [22,23]. Thus, we examined the effects of apigenin on LPS-stimulated inflammation in RAW264.7 macrophages.…”
Section: Apigenin Inhibits the Activation Of Tlr-4/nf-κb Pathway In Mmentioning
confidence: 99%
“…Notably, apigenin can ameliorate inflammation through inhibition of TLR-4 and NF-κB activation. In a mouse model of lung ischemia-reperfusion injury (LIRI), apigenin administration significantly reduced NF-κB activation and the expression levels of tumor necrosis factor-α (TNF-α), interleukine-6 (IL-6), and inducible nitric oxide synthase (iNOS) [22]. Zhang et al [23] demonstrated that apigenin could improve early brain injury (EBI) and protect against blood-brain barrier (BBB) disruption in subarachnoid hemorrhage rats by repressing TLR-4/NF-κB pathway-mediated inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Both the cyclic stretch and hepatic ischemia-reperfusion-induced HMGB1 expression were mediated through NF- κ B signalling pathways [ 27 , 28 ]. Other research has confirmed that pulmonary I/R injury can lead to NF- κ B activation [ 29 , 30 ]. Notably, TLR4 directly activates NF- κ B signalling pathways and the expression of proinflammatory cytokines such as IL-1 β and TNF- α [ 31 ].…”
Section: Discussionmentioning
confidence: 94%
“…Nrf2 has been shown to be an important transcription factor induced by the antioxidant response [10]. Nrf2 could activate a battery of antioxidant genes, HO-1, NQO1 and other genes, which regulated oxidative stress, inflammatory reactions and apoptosis in various disorders [12, 38, 39]. Furthermore, NF-κB is also an important transcription factor that plays an important role in redox changes [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proven that Nrf2 is an essential cytoprotective regulator considering genes encoding the expression of proteins of antioxidants, detoxification enzymes, and other mediators of stress response [11]. These genes confer the resistance to oxidative stress in various disorders, including catalase (CAT), superoxide dismutase (SOD), Glutathione S-transferase (GST), NADPH quinine oxidoreductase-1 (NQO1) and heme oxygenase-1 (HO-1) [12, 13]. In addition, nuclear factor kappa B (NF-κB), which can be activated by ROS in I/R injury, is one of the major redox-sensitive transcription factors controlling the expression of pro-inflammatory genes [14].…”
Section: Introductionmentioning
confidence: 99%